The Profile of Special Job Market of Vocational School in Kebumen Regency - Samidjo Samidjo (Jurnal Taman Vokasi, 2018)
The research was aimed to describe the profile and the management of special jobs recruitment of Vocational Schools in Kebumen Regency. The mandate of the special jobs recruitment is to facilitate the graduates of the schools to get jobs soon after their graduation. The research is a qualitative approach. The setting of the research was the Asociation of special jobs recruitment in the Kebumen Regency. The association consists of 59 schools, consisting of 29 business and management schools and 30 industrial technology schools. The data of the research were collected by using interview, observation, and documentation methods. The resources of the data were the head of the Asociation of special jobs recruitment, the managers of special jobs recruitment, teachers, principals, and the guidance and counselor teachers. The key informant was the head of the special jobs recruitment association in the Regency. The data were inductively analyzed, and the steps of data analysis using Miles and Huberman interactive model. The results of the research show that (1) the rate of recruitment of vocational high school graduates relatively high, (2) theÂ  graduates get the job facilitated by special jobs recruitment by the model of contract for 6 months to 2 years, (3) the graduates get the jobs not always in their competences as they were trained, (5) it is very rare the graduates get a permanent job after their first or second contract finish. The industries prefer to hire new graduates as job seekers rather than giving a permanent assignment. There is a concern that the graduates will be lost their job in their productive lifetime.